Delineating the Site of Interaction of the 5-HT(3A) Receptor with the Chaperone Protein RIC-3 - Pirayesh, Elham (Biophys J, 2020)
The serotonin type 3A (5-HT(3A)) receptor is a homopentameric cation-selective member of the pentameric ligand-gated ion channel (pLGIC) superfamily. Members of this superfamily assemble from five subunits, each of which consists of three domains: extracellular (ECD), transmembrane (TMD), and intracellular domain (ICD). Previously, we have demonstrated that the 5-HT(3A)-ICD is required for the interaction between 5-HT(3A) and the chaperone protein resistance to inhibitors of choline esterase (RIC-3). Additionally, we have shown that 5-HT(3A)-ICD fused to maltose-binding protein (MBP) directly interacts with RIC-3, without the involvement of other protein(s). To elucidate the molecular determinants of this interaction, we developed different MBP-fused 5-HT(3A)-ICD constructs by deleting large segments of its amino acid sequence. We expressed seven engineered ICDs in Escherichia coli and purified them to homogeneity. Using a RIC-3 affinity pull-down assay, the interaction between MBP-5HT(3A)-ICD constructs and RIC-3 was investigated. In summary, we identify a 24-amino-acid-long segment of the 5-HT(3A)-ICD as a molecular determinant for the interaction between the 5-HT(3A)-ICD and RIC-3.